How plants respond to heavy metal contamination: a narrative review of proteomic studies and phytoremediation applications - Jameel Rabee Jameel Al-Obaidi, Azi Azeyanty Jamaludin (Tanjung Malim, 2024)
How plants respond to heavy metal contamination: a narrative review of proteomic studies and phytoremediation applications by Jameel Rabee Jameel Al-Obaidi, Azi Azeyanty Jamaludin